2017
DOI: 10.1088/2043-6254/aa84d4
|View full text |Cite
|
Sign up to set email alerts
|

Fungal synthesis of size-defined nanoparticles

Abstract: [7] and silica oxide [8] NPs, which can be produced by mycofabrication-(NPs synthesis systems using fungi). Apart from fungi, there is a variety of microorganisms producing NPs, such as many bacteria, biofilms [9], actinomycetes [10] and extremophiles [11]. Apart from bacteria, fungi are a favorable option for NPs synthesis. Fungi are filamentous by nature and able to withstand the pressure of flow and mixing in the bioreactor trough. In addition, they can accumulate metals by biological and physicochemical me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 98 publications
0
35
0
Order By: Relevance
“…Compared to synthesis using plants, the mycelial mass of fungi is more resistant to agitation and pressure, so it is more suitable for large-scale syntheses (Velusamy et al, 2016). Furthermore, by adjusting culture conditions such as time, temperature, pH, and quantity of biomass, among others, it is possible to manipulate the metabolism of fungi so as to obtain nanoparticles with the desired characteristics, such as specific size and morphology (Zielonka and Klimek-Ochab, 2017).…”
Section: Biogenic Synthesis Of Silver Nanoparticlesmentioning
confidence: 99%
“…Compared to synthesis using plants, the mycelial mass of fungi is more resistant to agitation and pressure, so it is more suitable for large-scale syntheses (Velusamy et al, 2016). Furthermore, by adjusting culture conditions such as time, temperature, pH, and quantity of biomass, among others, it is possible to manipulate the metabolism of fungi so as to obtain nanoparticles with the desired characteristics, such as specific size and morphology (Zielonka and Klimek-Ochab, 2017).…”
Section: Biogenic Synthesis Of Silver Nanoparticlesmentioning
confidence: 99%
“…Multiple biological actions of the NPs such as antibacterial [ 2 , 3 ], antioxidant [ 2 , 4 ], anticancer [ 5 , 6 ], antifungal [ 5 , 7 ], antiviral [ 8 , 9 ], antiparasitic [ 10 , 11 ] and anti-inflammatory activities [ 12 , 13 ] have been associated with their highly diverse chemistry-rich characteristics [ 14 ]. There are myriad ways of synthesizing NPs, including physical (e.g., vapor deposition [ 15 ], sputter deposition [ 16 ], electric arc deposition [ 17 ], ion beam technique [ 18 ], molecular beam epitaxy [ 19 ], melt mixing [ 20 ]), chemical (e.g., co-precipitation [ 21 ], sol-gel [ 22 ], microemulsions [ 23 ], sonochemical synthesis [ 24 ] UV-initiated photoreduction [ 25 ]), and biological (e.g., synthesis using plant extracts [ 26 ], microorganisms [ 26 ], algae [ 27 ], fungi [ 28 ], animals [ 29 ] or agricultural waste [ 30 ], enzymes [ 31 ]) methods as well as hybrid methods [ 32 ] ( Figure 1 ). There are advantages and limitations for each synthetic method, and the choice of method is selected based on the downstream applications.…”
Section: Nanoparticles and Green Technologymentioning
confidence: 99%
“…Byproducts of mold metabolism have negative effects on structural or functional integrity of developing nervous system 41 . It is known that Aspergillus secretes enzymes and proteins in large amounts and can generate nanoparticles extracellularly 42 . As it was demonstrated by TEM in the current study, an abundance of nanoparticles was found in a child with ASD, but not in a control healthy person.…”
Section: Discussionmentioning
confidence: 99%